Elucidating the dynamics of carbamazepine uptake using date pit-derived activated carbon: A comprehensive kinetic and thermodynamic analysis - Ramez M. Zayyat; Rim Yahfoufi; Mahmoud Al-Hindi; Michel A. Kordahi; George M. Ayoub; Mohammad N. Ahmad (Heliyon)
Water contamination with pharmaceuticals such as Carbamazepine (CBZ) presents a significant environmental challenge. This study investigates the use of activated carbon derived from waste date pits (DPAC) for the removal of CBZ from water. The impact of several parameters such as pH, temperature, CBZ concentration, and flow rate on the adsorption were assessed. The generated DPAC demonstrated a specific surface area of 309 m2/g, a pore volume of 0.264 cm³/g, and the pores are mainly distributed at 1.86, 2.73, and 3.43 nm. The Langmuir, Freundlich, Sips, and Toth isotherms were used to fit the experimental data, and the results indicate the occurrence of monolayer adsorption and heterogeneous surface conditions. The Linear Driving Force model was used for kinetic analysis, showing improved fit at higher concentrations. Thermodynamic analyses revealed the process to be endothermic, spontaneous, and entropically driven. The DPAC achieved an adsorption capacity of 14.89 mg/g and maintained 94 % effectiveness after the first regeneration cycle and 70 % after four cycles. This study highlights the potential of DPAC as a sustainable adsorbent for advanced water purification.